Brand Positioning Radio Cakra 90.5 FM sebagai Radio Kearifan Budaya Lokal Kota Bandung - Rizky Akbar Rossano; Nova Yuliati (UNISBA Press, 2022)
Abstract. Brand positioning plays an important role in maintaining the image, existence and placing a product to the wider community. Is an activity that is able to develop and has a uniqueness in a company. The brand positioning carried out by Radio Cakra 90.5 FM carries out applications that will represent the radio, one of which is a form of activity, as well as the application of information that will become news in radio programs, as a form of credibility that Radio Cakra 90.5 FM does not only present a program related to music only. The context of the problem, the researcher uses the Symbolic Interactional Theory according to George Ritzer and Goodman (2007: 289) in order to strengthen the data from this study and Theory Brand Positioning according to Gelder (in, 2005:110). The purpose of this study was to determine the process and packaging of Verbal and Non-verbal symbols and the application of brand positioning of Cakra 90.5 FM Radio as a Local Cultural Wisdom Radio in the city of Bandung. The research uses a qualitative approach with a case study method. Yin (2009) is a holistic single-case study. From the results of this study it was found that Radio Cakra 90.5 FM uses the application of brand positioning in the form of off air, on air and online activities to maintain its identity as a radio of local cultural wisdom in the city of Bandung. As well as having unique programs, interesting music content, and simple forms of promotion that Radio Cakra 90.5 FM Bandung does in placing its identity to listeners. Abstrak. Brand positioning menjadi peran penting dalam mempertahankan citra, eksistensi serta menempatkaan suatu produk ke masyarakat luas. Merupakan sebuah kegiatan yang mampu mengembangkan serta memiliki keunikan disuatu perusahaan. Brand positioning yang dilakukan oleh pihak Radio Cakra 90.5 FM ini melakukan penerapan yang akan mewakili radio tersebut, salah satunya bentuk kegiatan, serta penerapan informasi yang akan menjadi sebuah berita di dalam program acara radio, sebagai bentuk kredibilitas bahwa Radio Cakra 90.5 FM ini tidak hanya menyajikan sebuah program yang berkaitan dengan musik saja. Konteks permasalahan tersebut peneliti menggunakan Teori Interaksional Simbolik menurut George Ritzer dan Goodman (2007:289) agar memperkuat data dari penelitian ini serta Teori Brand Positioning menurut Gelder (dalam, 2005:110). Tujuan dari penelitian ini untuk mengetahui proses serta pengemasa simbol-simbol Verbal dan Non-verbal dan penerapan brand positioning Radio Cakra 90.5 FM sebagai Radio Kearifan Budaya lok di kota Bandung. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus Penelitian studi kasus tunggal holistik (holistic single-case study) Yin (2009). Dari hasil penelitian ini didapatkan bahwa Radio Cakra 90.5 FM menggunakan penerapan brand positioning dalam bentuk kegiatan off air, on air dan online untuk mempertahankan identitas sebagai Radio kearifan budaya lokal di Kota Bandung. Serta memiliki program unik, konten musik yang menarik, dan bentuk promosi secara sederhana yang dilakukan Radio Cakra 90.5 FM Bandung dalam menempatkan identitasnya ke pendengar.